The Quakers in America - Hamm, Thomas D. (Columbia University Press, 2003)
Provides a concise history of the Religious Society of Friends, an introduction to its beliefs and practices, and a vivid picture of the culture and controversies of the Friends today.
Keywords: Society of Friends -- United States.; Société des Amis -- États-Unis.; RELIGION -- Christianity -- Quaker.; RELIGION -- General.; Society of Friends; United States